Ski profile characterization using different methods - Sandberg, J.; Hindér, G.; Almqvist, A.; Larsson, R. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: One of the most important factors affecting ski performance is the ski profile, which refers to the distance between the ski base and the contacting surface (snow or ice). Today, various methods are employed by manufacturers, professional racing teams, and amateurs to determine the best skis for specific conditions, based on factors such as the length and location of the glide zones, among others. This raises an important question: How accurate are the methods used to characterize these factors?